2003
DOI: 10.1097/01.sla.0000086664.90571.7a
|View full text |Cite
|
Sign up to set email alerts
|

Distal Aortic Perfusion and Cerebrospinal Fluid Drainage for Thoracoabdominal and Descending Thoracic Aortic Repair

Abstract: Use of adjunct over a long period of time has produced favorable results; approximately 1 neurologic deficit saved for every 20 uses of adjunct overall. In extent II aneurysms, where the effect is greatest, this increases to 1 saved per 5 uses. Adjunct is also associated with long-term survival, which is consistent with mitigation of ischemic end-organ injury. These long-term results indicate that cerebrospinal fluid drainage and distal aortic perfusion are safe and effective adjunct for reducing morbidity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
196
0
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(207 citation statements)
references
References 13 publications
5
196
0
6
Order By: Relevance
“…These include epidural cooling, distal aortic perfusion and cerebrospinal fluid drainage. [2][3][4] To establish new approaches to protect the spinal cord from ischemic damage, a better understanding of the various processes triggered by an insufficient blood supply to the spinal cord is required. The most promising strategy would be to activate endogenous neuroprotective pathways before the surgical procedure and thus, increase the resistance of spinal cord neurons to a transient interruption of blood supply.…”
Section: Introductionmentioning
confidence: 99%
“…These include epidural cooling, distal aortic perfusion and cerebrospinal fluid drainage. [2][3][4] To establish new approaches to protect the spinal cord from ischemic damage, a better understanding of the various processes triggered by an insufficient blood supply to the spinal cord is required. The most promising strategy would be to activate endogenous neuroprotective pathways before the surgical procedure and thus, increase the resistance of spinal cord neurons to a transient interruption of blood supply.…”
Section: Introductionmentioning
confidence: 99%
“…Crawford et al [44] performed a prospective randomized study on the effectiveness of CSF drainage for preventing paraplegia and reported that it was not beneficial in this regard. Conversely, a more recent prospective randomized study of CSF drainage by Coselli et al, [45] and a report by Safi et al, [46] showed that CSF drainage did help to prevent spinal cord injury. Many reports regarding reversal of paraplegia by commencing CSF drainage after surgery or endovascular stent-grafting also substantiated the importance of lowering the CSF pressure.…”
Section: Cerebrospinal Fluid Drainagementioning
confidence: 98%
“…Various methods have been devised to protect against spinal cord ischemia during surgery for TAA (Bicknell et al, 2009;Tabayashi, 2005), such as cerebrospinal fluid drainage (Acher et al, 1994;Coselli, et al, 2002;Fedorow et al, 2010;Griepp et al, 1996;Griepp & Griepp, 2007), hypothermia (Griepp et al, 1996), epidural cooling (Cambria et al, 1997), monitoring of somatosensory (SSEP) (Crawford et al, 1988) and motor evoked potentials (MEP) (de Haan et al, 1997;Jacobs et al 2006), intercostal artery reattachment (Acher et al, 2008), distal aortic perfusion (Crawford et al, 1988;Safi et al, 2003), and direct spinal cord cooling (Davison et al, 1994). Spinal cord perfusion is regulated according to the following formula,…”
Section: Prevention Of Paralysis During Surgerymentioning
confidence: 99%
“…However, in a prospective study, SSEP monitoring and temporary distal aortic perfusion did not reduce the prevalence of early or delayed neurologic complications after surgery for thoracic aortic aneurysm (Crawford et al, 1988 Table 3. The effects of distal aortic perfusion (DAP) and cerebrospinal fluid drainage (CFD) (Safi et al, 2003) After the release of the cross-clamp, the spinal cord is at further risk of ischemia secondary to hypercapnia and hypotension, which can result in decreased tissue perfusion. Metabolic acidosis after the release of the cross-clamp causes an increase in cerebral blood flow, resulting in increases in intracranial pressure and cerebrospinal fluid pressure (Fedorow et al, 2010), which increase tissue back pressure, leading to decreased spinal cord perfusion due to ischemia.…”
Section: Prevention Of Paralysis During Surgerymentioning
confidence: 99%